Study on development, validity and reliability of a risk-screening questionnaire for alcohol and drug use - Kültegin Ögel; Ceren Koç; Serap Görücü (Psychiatry and Clinical Psychopharmacology, 2017)
Objective: The objective of this study is to develop a risk-screening questionnaire appropriate for cultural characteristics in detection of alcohol- and drug-use level through utilization of Addiction Profile Index (API) and perform the reliability and validity work thereof. Methods: The study was carried out on the sample of two previously made separate studies. Both samples were selected from inmates in prisons. API, CAGE Scale, Alcohol Use Disorders Identification Test (AUDIT), Drug Abuse Screening Test (DAST-10), Drug Use Disorders Identification Test (DUDIT) and clinical interview form structured for DSM-IV-TR (SCID-I) were employed in the study. Results: BAPİRT-alcohol and BAPİRT-drug questionnaires evaluating alcohol and drug abuse separately and each of which consisting of six questions were developed. Cronbach's alpha coefficients were found as 0.70 and 0.88 in the internal consistency analysis made with sample 1 data of BAPİRT alcohol and drug scale respectively. BAPİRT alcohol scale consists of two components while BAPİRT drug questionnaire comprises a single component. BAPİRT-alcohol questionnaire was found to correlate with BAPİ (Bağımlılık Profil İndeksi, Addiction Profile Index), AUDIT and CAGE by 0.94, 0.92 and 0.78 respectively. BAPİRT- drug questionnaire was found to correlate with BAPİ, DUDIT and DAST by 0.96, 0.89 and 0.81 respectively. BAPİRT for alcohol had sensitivity and specificity scores of 93.8%, and 72.5%, respectively, when using the cut-off score of 3 while BAPİRT for alcohol had sensitivity and specificity scores of 91.7% and 92.3%, respectively, when using the cut-off score of 4. Conclusions: These findings support that APIRS questionnaires are reliable and valid drug abuse screening instruments in Turkish patients with alcohol and drug use. Further studies need to be done in different clinical populations.